Self-Consciousness and the Priority Question: A Critique of the “Sensibility First” Reading of Kant - Ellis, Addison (Universidad Panamericana. Facultad de Filosofía, 2022)
This essay presents a critique of what Robert Hanna has re-cently called the “sensibility first” reading of Kant. I first spell out, in agreement with Hanna, why the contemporary debate among Kant scholars over conceptualism and non-conceptu-alism must be understood only from within the perspective of what I dub the “priority question”—that is, the question wheth-er one or the other of our “two stems” of cognition may ground the objectivity and normativity of the other. I then spell out why the priority question may be asked only from within the per-spective of self-consciousness. Specifically, the central issue to be dealt with is how what Kant calls the original combination of understanding and sensibility is a synthesis internal to an act of self-consciousness. Only then can we ask what that original synthesis might tell us about the possibility of prioritizing one capacity over another in a story of cognition generally. Once we see the central issue more clearly, then I will look at the “sen-sibility first” view in its most general form and propose that it should be criticized for its failure to account for Kant’s notion of an objective unity of self-consciousness
La autoconciencia y la cuestión de la prioridad: una crítica de la lectura de Kant de “la sensibilidad primero”
Introduction -- 1. The centrality of self-consciousness to the priority question -- 1.1 The apparent dualism of unity -- 1.2 Synthetic unity as simple self-consciousness -- 1.3 Difference inside unity -- 2. The possibility of a sensibility first reading of Kant -- 2.1 A problem for SF as unity dualism -- 2.3 Hanna’s organicist alternative -- 2.3.1 Potential problem 1: a regress of syntheses -- 3. Problem 2: the problem of the objective unity of self-consciousness -- 4. Conclusion
Keywords: Kant; Autoconciencia; Sensibilidad; No conceptualismo; Self-consciousness; Sensibility; Non-conceptualism